Data Envelopment Analysis on Efficiency of Insurance Companies in Ethiopia - Sharew, Ashagrie; Fentie, Gizachew (American Scientific Research Journal for Engineering, Technology, and Sciences, 2018)
Competition in the economy can create a positive prospect for economic growth and development of a country. Competition in Ethiopian financial sector in general and insurance industry in particular should be strong enough for enhancement of efficiency, provision of better service to customers, greater innovation and lower prices thus resulting in improvement of consumers welfare and overall economic growth of the country.This research is developed to conduct a study to empirically assess the efficiency of the insurance companies in the Ethiopian insurance industry. Data Envelopment Analysis (DEA) approaches was used to measure the efficiencies of the insurance companies. The proposed study attempted to address (focus) on what is the efficiency of the insurance companies in Ethiopia? What factors affect their efficiency? In what mechanism the insurance companies in Ethiopia could improve or enhance their efficiency? These and other related issues have not been largely answered and not empirically supported in the Ethiopian context. In general the study seeks to find the determinants of the insurance companies’ ‘performance/efficiency’. In order to achieve this objective, the study used Panel data covering ten years period from 2006– 2015. The proposed study attempted to provide its contributions to the literature, policy, managerial and methodological implications. Based on the result Ethiopian insurance corporation and Nyala insurance company were relatively efficient taking first and second rank respectively. It was found that company size and number of branches were significantly affecting efficiency score at 95% confidence.